2020
DOI: 10.1021/acs.estlett.0c00505
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Relevance of Superoxide in PFOA Degradation

Abstract: Perfluorooctanoic acid (PFOA) is a widely distributed recalcitrant contaminant. In recent years, advanced oxidation processes have been explored for PFOA degradation, yet factors influencing their efficacy and degradation mechanism are not fully understood. Here, we resolve ambiguity in the literature regarding the role of superoxide in PFOA degradation (e.g., by nucleophilic attack) by considering three pure superoxideproducing systems: KO 2 in dimethyl sulfoxide, xanthine oxidase with hypoxanthine, and WO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 45 publications
(68 reference statements)
3
18
0
Order By: Relevance
“…61,62 Superoxide, which is abundantly obtained from reductive photocatalysis, is also known to be relatively ineffective for the degradation of perfluorooctanoic acid (PFOA). 63 While the cleavage of the C−F bond in PFOA using photogenerated holes has been demonstrated using boron- 64 and bismuth-based photocatalytic materials, 65 it requires very high valence hole potentials above 4 eV (vs NHE).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61,62 Superoxide, which is abundantly obtained from reductive photocatalysis, is also known to be relatively ineffective for the degradation of perfluorooctanoic acid (PFOA). 63 While the cleavage of the C−F bond in PFOA using photogenerated holes has been demonstrated using boron- 64 and bismuth-based photocatalytic materials, 65 it requires very high valence hole potentials above 4 eV (vs NHE).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, defluorination of poly- and perfluoroalkyl substances (PFASs) was explored to more efficiently utilize the conduction band electrons produced by the photocatalyst and to more thoroughly investigate the unique properties that emerge with downsizing the Pt cocatalyst to the atomic scale. PFAS have garnered significant attention in recent years, due to elevated concerns regarding their potential human health risks and persistence in the environment due to the high C–F bonding and dissociation energy (∼450 kJ mol –1 ). , Conventional AOPs are often ineffective in the treatment of PFAS, as these compounds have negligible reactivity toward •OH. , Superoxide, which is abundantly obtained from reductive photocatalysis, is also known to be relatively ineffective for the degradation of perfluorooctanoic acid (PFOA) . While the cleavage of the C–F bond in PFOA using photogenerated holes has been demonstrated using boron- and bismuth-based photocatalytic materials, it requires very high valence hole potentials above 4 eV (vs NHE).…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitous presence of recalcitrant per- and poly fluoroalkyl substances (PFAS) in the natural and engineered aqueous environment is well documented. , These forever chemicals undergo long-range transport through air and water. , In addition, these are challenging to destroy due to the strength (544 kJ/mol) and the shielding effect of polar covalent C–F bonds from negatively charged reactive oxygen species. PFAS are also highly resistant to biodegradation due to microbial inaccessibility of the carbons and these molecules being poor electron donors , although recent studies showed that biodegradation can potentially be achieved with pure cultures of microorganisms in well-controlled laboratory settings over weeks/months. As a result, nondestructive remediation and treatment strategies are deemed pragmatic and necessary to remove PFAS from water. Granular activated carbons (GAC)/ion exchange resins in the engineered water treatment and remediation systems, geoliners in landfills, as well as containment barriers in emission control in the incinerators are interventions and can contain and remove PFAS from the natural environment. The containment or adsorption of PFAS (e.g., by GAC) are imperative measures; however, inadequate disposal, transportation, and storage of the PFAS-laden adsorbents can introduce PFAS back into the environment .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of superoxide anions(•O 2 − ) can be detected using nitrotetrazolium blue chloride (NBT). The •O 2 − anions can combine with NBT in DMSO solution to produce a blue-violet compound that can be detected at 529nm [ 38 ]. We discovered the presence of •O 2 − in solutions of both forms of ZIF-8 when they are illuminated ( Figure 3 C,D).…”
Section: Resultsmentioning
confidence: 99%